2005
DOI: 10.1073/pnas.0503437102
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of ΔNp63 and the migration of ocular limbal cells in human corneal regeneration

Abstract: The p63 gene generates transactivating and N-terminally truncated transcripts (⌬Np63) initiated by different promoters. Alternative splicing gives rise to three different C termini, designated ␣, ␤, and ␥. In the ocular epithelium, the corneal stem cells, which are segregated in the basal layer of the limbus, contain the ␣ isoform but not ␤ or ␥. Holoclones derived from the limbus are rich in ␣, meroclones contain little, and paraclones contain none. In normal resting corneal epithelium, p63 of all isoforms is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
320
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(344 citation statements)
references
References 29 publications
18
320
0
2
Order By: Relevance
“…It was also shown that antibodies detecting all isoforms of p63 identified differentiated cells as well (66). The isoform DNP63a was later shown to identify epithelial stem cells, whereas b and c isoforms have been shown to promote epithelial cell differentiation (67,68). At present, DNp63a is considered as a reliable marker of both resting and activated limbal epithelial stem cells (47).…”
Section: Molecular Markers Of Lescsmentioning
confidence: 99%
“…It was also shown that antibodies detecting all isoforms of p63 identified differentiated cells as well (66). The isoform DNP63a was later shown to identify epithelial stem cells, whereas b and c isoforms have been shown to promote epithelial cell differentiation (67,68). At present, DNp63a is considered as a reliable marker of both resting and activated limbal epithelial stem cells (47).…”
Section: Molecular Markers Of Lescsmentioning
confidence: 99%
“…In contrast, the SC-containing limbal epithelium has a high proliferative potential in different cultures [12][13][14][15], and their in vitro proliferation is resistant to the inhibition by tumor-promoting phorbol esters [13,16,17]. Furthermore, limbal basal epithelial cells express cytokeratin 19 [18], and integrin a9 [10,19], and preferentially express such progenitor markers as p63 [20], especially its ∆Np63a isoform [21,22], Bcrp1/ABCG2 [10,[23][24][25], and N-cadherin [26].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal CD157 appears as a doublet with a M r of 42-to 45-kDa, suggesting the existence of different isoforms, likely produced by alternative glycosylation (35) Epithelium regenerates during wound repair by migration of cells from the corneal limbus (1,28). However, an open issue in corneal regeneration is the lack of a dependable surface marker of the limbal stem cell population (41).…”
Section: Discussionmentioning
confidence: 99%
“…The protein was more apparent in the cells at the center of each cluster, which in turn tended to accumulate at the palisades of Vogt (see Figure 4A), a region of the limbus that harbors the highest concentration of stem cells (1,27). Nuclear p63 antigen is a putative marker of limbal stem cells (28) and, according to merged-double staining, p63 + was coexpressed with CD157 within the basal limbal layer (see Figure 4C). CK19 is expressed by limbal and peripheral corneal epithelial cells (29), suggesting that CD157 and CK19 may express partially overlapped patterns.…”
Section: Topographical Localization Of Corneal Cd38 and Cd157mentioning
confidence: 99%